Use of Digital Media for Sex Education in Early Childhood with Low-Income Parents - Susianty Selaras Ndari; Khusniyati Masykuroh; Amelia Vinayastri; Kibitiah Kibitiah (Madrosatuna: Journal of Islamic Elementary School, 2021)
This study aims to explore the use of digital smartphone media for sexuality education of children with low-income parents by emphasizing the usage of digital media for protection from sexual violence against children. This research method uses case studies with children (aged 3-6 years) in 25 low-income families. Data collection was carried out for eight rounds using an ecocultural approach to examine the experiences of children and parents in using digital media technology for sex education for children aged 3-6 years. This research explains 1) What technology is used by children at home ?, 2) what is the role of parents at home in helping children in providing sex education learning using digital media ?, 3) What are the benefits of using digital media for sex? education for children? This is done because of the adaptation of technology to the curriculum for early childhood education. Due to the increasing use of digital media in all layers of parents, so the use of digital technology can help children to learn to increase their knowledge of sexuality. So they can protect themselves from sexual violence.